Interim results from the ELiPSE-1 study: A phase 1, multicenter, open-label study of CNTY-101 in subjects with relapsed or refractory CD19-positive B-cell malignancies - Namburi, Swathi; Latif, Tahir; Oluwole, Olalekan O.; Cross, Scott J.; Simmons, Gary; Iragavarapu, Chaitanya; Hu, Bei; Jih, Gloria; Bullaughey, Kevin; Das, Poulomee A; Devlin, Elizabeth; Flowers, Kevin; et al. (Journal of clinical oncology, 2024)
7023Background: CNTY-101 is an allogeneic, iPSC-derived anti-CD19 Chimeric Antigen Receptor NK (CAR-iNK) cell product with Allo-Evasion edits to avoid host rejection. Potential benefits of CNTY-101 include immediate availability for treatment, repeat dosing without the need for lymphodepletion, and the potential for improved safety over T-cell based therapies. The first-in-human Phase 1 clinical trial of CNTY-101, ELiPSE-1 (NCT05336409), evaluates safety, preliminary efficacy, PK, and translational biomarkers in patients with CD19-positive B-cell malignancies. Methods: Subjects with R/R aggressive and indolent B-cell NHL received lymphodepletion (LDC) followed by assignment to 100e6, 300e6 or 1e9 cells at either Day 1 (Schedule A) or Days 1, 8 and 15 (Schedule B). Eligible subjects (ie, achieved SD or better at Day 28 by PET/CT) can receive additional cycles, with or without one additional regimen of LDC. Subjects also receive daily subcutaneous injections of IL-2 for 8 days (A) or 4 days (B) following each infusion. Results: At time of abstract submission, 10 subjects have been treated (n=4 DL1A; n=3 DL2A; n=2 DL3A; n=1 DL2B). Three subjects (1 at DL1A, 2 at DL2A) received additional cycle(s) of CNTY-101. Three subjects have not yet been evaluated for full safety and efficacy within the DLT window. Seven subjects (n=5 DLBCL; n=1 FL; n=1 MZL) had data available as of the data cut (Nov 30, 2023). All had stage 4 disease, 6/7 were refractory to last line of therapy, with a median of 4 (2-5) prior lines of therapy including CAR T (3/7). No DLTs, GvHD or ICANs were observed. Two subjects had cytokine release syndrome (n=1 Gr 1, n=1 Gr 2), all responding promptly to treatment. ORR/CRR was 25%/25% for 100e6 cells (DL1A) and 67%/33% for 300e6 cells (DL2A). Dose escalation is ongoing. In subjects from all three dose levels, CNTY-101 rapidly traffics out of circulation after infusion and is observed via cell-free DNA on Day 3 and detected up to 28 days. CNTY-101 persistence was not adversely impacted when given without lymphodepletion in two subjects who received additional cycles of CNTY-101. Induction of functional humoral immunogenicity against CNTY-101 was not observed at any of the dose levels, regardless of single or multiple cycles of CNTY-101. Adaptive immune responses were observed in the tumor microenvironment on Day 8. Conclusions: CNTY-101 administered as a single dose in multiple cycles has demonstrated a manageable safety profile and preliminary evidence of efficacy. Allo-Evasion edits may allow for repeat dosing for multiple cycles without allorejection in the absence of lymphodepletion. Preliminary efficacy supports dosing at higher dose levels and with more dose-intense regimens. Updated safety, efficacy, PK, and CNTY-101's impact on tumor for DL3A and DL2B will be provided. Clinical trial information: NCT05336409.